Mechanisms underlying the impact and interaction of temperature and UV‐B on the hatching of spider mite and phytoseiid mite eggs. Issue 10 (18th July 2022) - Yuan, Lifeng; Osakabe, Masahiro
Abstract: BACKGROUND: A spider mite control method using night‐time ultraviolet (UV)‐B irradiation was recently developed for strawberry greenhouses (UV method). The control effect of this UV method is negatively affected by increasing temperature. Tetranychus urticae eggs are more resistant to a single dose of UV‐B irradiation than Neoseiulus californicus eggs. By contrast, N. californicus can better survive nightly UV‐B irradiation with the UV method compared with T. urticae . To elucidate the mechanism underlying these phenomena, we explored the hypotheses that higher temperature promotes photoenzymatic repair (PER) and that mortality is determined by UV‐B susceptibility in the embryonic stage exposed to UV‐B. RESULTS: PER efficacy was not promoted by increasing temperature. The lowest hatchability (around zero) of T. urticae eggs after a single dose of UV‐B irradiation (0.288 and 0.432 kJ m −2 ) without photoreactivation was seen in the morphogenesis stages between "cleavage ended" and "eye points became colored". Based on these results, we developed a linear function of daily UV‐B irradiance and deviation of cumulative irradiance during vulnerable embryonic developmental phases from 50% lethal dose (LD50 ) after a single dose of UV‐B irradiation. The difference between T. urticae and N. californicus and changes in UV‐B vulnerability due to temperature could be explained by this simple relationship. CONCLUSION: Slower development in T. urticae than N. californicus in nature and developmental delay under low temperatures increase the ovicidal effects of the UV method. This shows the advantage of the simultaneous use of the UV method and biological control, contributing to the development of integrated pest management. © 2022 Society of Chemical Industry. Abstract : Slower development in Tetranychus urticae than Neoseiulus californicus in nature and developmental delay under low temperatures increase the ovicidal effects of the ultraviolet (UV) method. This shows the advantage of the simultaneous use of the UV method and biological control, contributing to the development of integrated pest management.